HOW COULD NATURAL DISASTERS AFFECT RURAL ADULT'S ELDER CARE PREFERENCE IN WESTERN CHINA?. (11th November 2018) - Guo, M
Abstract: Understanding people's preference of aging services in disaster prone areas has always been important. This information has been used to improve the efficiency of resource allocation for post-disaster reconstruction, especially in disaster affected areas in rural western China where funds and resources are both limited. We conducted the Disaster Relief and Elder Care Project to collect data on older adults (n=811) in Baoji, Shaanxi Province. This community is an area with low economic levels, serious age related problems, and frequent disasters. Logistic regression was used to test the hypothesis that financial losses from natural disasters affected people's aging services preference. The results showed that the respondents who had experienced financial losses in disasters were more likely to choose community care over home care than those who hadn't been adversely affected (p =0.000). The study indicated that the resources of disaster-affected areas should be directed toward enhancing community-based infrustucture.